Solution Combustion Synthesis, Characterization and Photocatalytic Activity of Nanosized ZnO Catalyst for Textile Industrial Dye Effluents Degradation - Nagaraja, R.; Girija, C.R.; Nagabhushana, B.M.; Donappa, N.; Manjunatha Sastry, K. (Asian Journal of Chemistry, 2011)
We report here the synthesis of ZnO nanoparticles by solution-combustion method employing a mixture of zinc nitrate and sugar (O/F = 1) as reactants. Powder X-ray diffraction, scanning electron microscopy and ultraviolet-visible absorption spectra were employed to characterize the product. The studies showed that the ZnO nanoparticles could be used to catalytically degrade organic dyes present in waste water of textile dye effluent under UV light irradiation. More than 95 % decolourization of textile dye effluent occurs with ZnO as catalyst with in 8 min at basic medium under solar light. It was also found that chemical oxygen demand takes place at a faster rate under solar light as compared to that under UV light. The results further suggest that, ZnO nanoparticles are better catalyst than the calcined ZnO under solar and UV light irradiation.